Factors Associated with Diarrhea in Toddlers 1-5 Years Old in the Work Area of Pamatang Raya Health Center Simalungun Regency in 2018 - Jumadiah Wardati BR Saragih (Science Midwifery, 2018)
Diarrhea is a condition where the frequency of bowel movements is more than 4 (four) times in infants and more than 3 (three) times in children. occurs as a result of a person's lack of information or knowledge. This research was conducted in the Pamatang Raya Public Health Center, Simalungun Regency from August to September 2018, a sample size of 71 people using quantitative methods that are analytic through a cross-sectional approach. Data collection using secondary data was analyzed using the bivariate chi-square test. The results showed that in the good knowledge category as many as 15 people (21.1%), sufficient knowledge 26 people (36.6), less knowledge 30 people (42.3), negative attitudes as many as 47 people (66.2%), positive attitudes as many as 24 (33.4), good mother behavior as many as 26 people (36.6), less behavior as many as 30 people (42.3%). The conclusion of the study is that there is a relationship between knowledge, attitudes, and behavior of mothers on diarrheal diseases in toddlers at Pematang Raya Public Health Center.